Integration between Lean, Six Sigma and Industry 4.0 technologies. (3rd November 2021) - Kumar, Pramod; Bhadu, Jagdish; Singh, Dharmendra; Bhamu, Jaiprakash
In the present decade, the manufacturing scenario is changing from the mass production to customised production with the advent of Industry 4.0 (I4.0). It has been also observed from the recent literature that there is a significant paradigm shift in the manufacturing system towards smart manufacturing or Industry 4.0. This has happened due to the adoption of advanced information/digital system along with latest technologies in the organisations. Lean and Six Sigma are the productivity and quality improvement methodologies for elimination of wastes and process variations respectively. In this paper, an attempt has been made to explore the interrelation between Lean, Six Sigma and Industry 4.0. It highlights the synergies among the concepts and technologies between these three domains with their interdependencies. Industry 4.0 creates a right platform to bring ample manufacturing capabilities to the next top level. It is clear that Lean and Six Sigma are basically data driven technologies and the new industrial paradigm can provide the right amount of informative data to strengthen these quality improvement approaches. Proper implications of Industry 4.0 technologies can boost the effectiveness of these two quality improvement techniques. The interdependencies of Lean Six Sigma, artificial intelligence and big data are also elaborated.